Regional intra-arterial vs. systemic chemotherapy for the treatment of advanced pancreatic cancer: a systematic review and meta-analysis - Cao, Yanjie; Yu, Dedong; Wu, Yun; Zhu, Wei (Frontiers in Oncology, 2024)
Introduction Pancreatic cancer is a highly aggressive malignancy with limited response to chemotherapy. This research aims to compare the effectiveness and safety of regional intra-arterial chemotherapy (RIAC) with conventional systemic chemotherapy in treating advanced stages of pancreatic cancer. Methods A comprehensive literature review was conducted using databases such as PubMed, Embase, Web of Science, and the Cochrane Library. Studies assessing the comparative outcomes of RIAC and systemic chemotherapy were included. Data extraction and quality evaluation were performed independently by two researchers. Statistical analysis was conducted using STATA16 software, calculating odds ratios (OR), risk differences (RD), and 95% confidence intervals (CI). Results Eleven studies, comprising a total of 627 patients, were included in the meta-analysis. The findings showed that patients undergoing RIAC had significantly higher rates of partial remission (PR) compared to those receiving systemic chemotherapy (OR = 2.23, 95% CI: 1.57, 3.15, I2= 0%). Additionally, the rate of complications was lower in the RIAC group (OR = 0.45, 95% CI: 0.33, 0.63, I2= 0%). Moreover, patients treated with RIAC had notably longer median survival times. Discussion The results of this research indicate that RIAC is associated with a higher rate of partial remission, improved clinical benefits, and fewer complications compared to systemic chemotherapy in the management of advanced pancreatic cancer. These findings suggest that RIAC may be a more effective and safer treatment option for patients with advanced stages of pancreatic cancer. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42023404637.